Tissue-specific contribution of macrophages to wound healing - Minutti, Carlos M.; Knipper, Johanna A.; Allen, Judith E.; Zaiss, Dietmar M. W. (Seminars in Cell & Developmental Biology, 2017)
Macrophages are present in all tissues, either as resident cells or monocyte-derived cells that infiltrate into tissues. The tissue site largely determines the phenotype of tissue-resident cells, which help to maintain tissue homeostasis and act as sentinels of injury. Both tissue resident and recruited macrophages make a substantial contribution to wound healing following injury. In this review, we evaluate how macrophages in two fundamentally distinct tissues, i.e. the lung and the skin, differentially contribute to the process of wound healing. We highlight the commonalities of macrophage functions during repair and contrast them with distinct, tissue-specific functions that macrophages fulfill during the different stages of wound healing.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Extra-cellular matrix; Inflammation; Lung; Macrophage; Skin; Tissue repair